HIGH-DOSE FLUOROQUINOLONES IN TREATMENT OF ACUTE SINUSITIS - S. V. Ryazantsev; K. I. Sapova (Медицинский совет, 2017)
Advantages and disadvantages  of  the  various classes  of  antibiotics is  argued, in particular effectiveness  and safety  of Levofloxacini  (Levolet R) in treatment of acute and of exacerbation of chronic diseases  in otolaryngology. The evolution of methods of treatment with these  products, summed up the preliminary results of research. Relevant information about the effectiveness and convenience of the new dosing with a pronounced therapeutic result is given.